(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The study was conducted in Dukhula sadar and Gasabari forest range under Madhupur Sal Forest of Bangladesh to determine the soil nutrient composition and isolation of fungi with varying stands. Three stands viz. pure sal, plantation and mixed were considered as treatment of the study. A quadrate sample plot of 10×10 m2 size was measured to collect soil samples for both chemical analysis and fungi isolation. Soil pH, electrical conductivity, organic matter content, total N, available P, exchangeable K, available S, fungal abundance and colony character (cm) were determined to achieve the objective of the study. The results revealed that soil pH and electrical conductivity were highest (6.61 and 21.10?S/cm) in mixed stand and lowest (6.38 and 10.75?S/cm) in pure stand. Organic matter content and total N were highest (2.24 and 0.145%) in plantation stand and lowest (1.65 and 0.112%) in mixed and pure stand, respectively. Available P, exchangeable K and available S were highest (3.65, 98.66 and 17.53ppm) in pure stand and lowest (1.97, 79.49 and 10.25ppm) in plantation stand. In addition, four fungal genera Sclerotium, Rhizoctonia, Pythium and Verticillium were identified in the study area soils. The highest fungal population (entire genus except Verticillium) (colony number/g soil) was found in mixed stand while it was found lowest in pure (Sclerotium ) and plantation stand (Rhizoctonia and Pythium ). There was no significant variation in colony diameter of the fungi among the treatments. Therefore, it can be concluded that better soil health was maintained in natural forest rather than plantation forest. Res. Agric., Livest. Fish.2(1): 17-25, April 2015